Pattern of consumption budget allocation by the poor families - Rizal Edy Halim; Imam Wahyudi; M. Budi Prasetyo (Universitas Hayam Wuruk Perbanas, 2015)
Various allegations towards the poverty problems are due to the issue of cultural, consumption behavior, social dynamics, and policy support. This study deals with the pattern of communities spending behavior through modeling the allocation of house-hold expenditure using secondary data published by Indonesian Central Bureau of Statistic (BPS) and offers models of household expenditure allocation appropriate and proportional. Allocation model of household expenditure is expected to be one step in formulating policies related to alleviate poverty. Time series analysis was used through modeling, econometric modeling and exposure effects going from the various patterns portrayed in the 2000-2008 period. By using National Economic Survey data (SU-SENAS) period 2000-2008, the study found that the differences in geological structure affect their livelihoods and consumption patterns, such as mountains, valleys, beaches, flood plains, lakes, and so on. The allocation of income of poor households tends to appear dominant in some categories of consumption related to housing and household facilities, various goods and services, clothes, and rice. However, other consumption categories tend not to be a priority for the consumption of poor households. Almost all categories of movement patterns of consumption have almost the same, still increasing from 2000 - 2006, except in 2005 which increased exceeding anomaly in 2006.